Benefits of sporting and recreational content in tourism animation programmes - Đorđević Saša (University Educons, Faculty of Sports and Tourism, Novi Sad, 2017)
Sports and recreational activity programmes in tourism are an important part of modern animation and tourism offer, causing great curiosity and interest of tourists in their implementation, as they are related to the use of available opportunities to maintain and increase the tourists' psychological and physical health. They are based on some of the fundamental principles of efficient tourism animation activities (freedom of choice, suitability to inclinations and preferences, direct involvement of tourists in realisation, interpersonal communication, dynamics of this tourist segment, etc). Such treatment of sporting and recreational programme, in addition to realistic expectations in terms of strengthening of the body and spirit through their realisation, make consideration of the benefits of sporting and recreational contents in programmes of tourist animation, as well as the role and importance of sporting and recreational animation programmes in tourism, extremely useful and justified. In this context, starting from the knowledge that health can not only be preserved, but also improved, this paper primarily treats issues related to building of adequate motivation of tourists for the realization of programmed sporting and recreational contents; for a direct involvement of tourists in the realization of sporting and recreational animation programmes; as well as issues related to health effects, as the most important outcomes and goals of realisation of sporting and recreational contents in tourism animation programmes.